Leitura e anotação no ambiente digital: uma pesquisa sobre o desempenho de leitura mediada pela plataforma DLNotes em um contexto pedagógico - Busato, Lucas Granado (2025)
Considering the changes that technology has brought to the relationship with written texts and pedagogical practices, this study aims to examine how annotations influence and can demonstrate the reading level of students from the Language and Literature program at UTFPR (Curitiba and Pato Branco campuses) when reading opinion articles in a controlled and digital environment. Employing a quantitative methodology followed by a qualitative analysis through data crossreferencing, a practical test was conducted with 153 university students, based on comparing the reading and annotation of a printed text with reading and annotation in a digital environment, mediated by the DLNotes platform. To assess the level of reading, a concept discussed by Wolf (2019) and Liberato and Fulgêncio (2010), the volunteers were subjected to a comprehension test of the opinion articles read, based on the retrieval of their annotations, which in this context is regarded as a textual genre, according to Moraes and Cavalcanti (2016). The test results showed that the overall performance of the students was better in the questionnaire based on the text provided on the DLNotes platform, as it allows for an improvement in the metacognitive skills —according to Jou (2016) — involved in the process of reading and annotating.